Evaluation of proximate composition, microbial load and sensory characteristics of instant holat as traditional spice in North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Maser WH, Sinaga MZE. 2021. Evaluation of proximate composition, microbial load and sensory characteristics of instant holat as traditional spice in North Sumatra. Biodiversitas 22: 3440-3445. Holat is the name of traditional food from North Sumatra, Indonesia which has astringent flavor derived from the bark of Phyllanthus emblica. The aims of this study were to determine the proximate composition and evaluate microbial load, and sensory characteristics of instant holat spice. There were 12 treatments, namely the combination of different amounts of bark (15 g, 25 g, 35 g, 45 g) and drying time (20 h, 22 h, 24 h). The proximate composition (moisture, ash, protein, fat, crude fiber, fat, and total carbohydrate content), microbial analysis (total plate count; yeast and mold count), and sensory characteristics (aroma, color, taste, and overall acceptability) were carried out. The results showed that water, protein, fat, crude fiber, and total carbohydrates contents were all significantly different (p < 0.05), except ash content. There was no yeast, mold, and bacterial growth on total plate count. There were no significant differences in all sensory characteristics (aroma, color, taste, and overall acceptability) of instant holat before and after brewing (p ? 0.05). The treatment of F4-24 was the best formula and has the highest score that might be developed as a product of instant holat spice. Further study should be conducted to determine the effect by increasing the amount of bark and evaluating its bioactivity.
Keywords: Instant holat spice; Phyllantus emblica bark; proximate composition; sensory characteristics; Sumatera Utara